2011
DOI: 10.1097/cnq.0b013e318204809b
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing Excellence

Abstract: Oral hygiene in seriously ill patients is a nursing responsibility. Oral hygiene regimens in conjunction with standardized ventilator-associated pneumonia "bundles" reduce the incidence of pneumonia, length of stay, and associated costs in critical care. Following strict adherence to the recommended ventilator-associated pneumonia bundle, the ventilator-associated pneumonia rate at the Northeast Baptist Hospital intensive care units has remained 0% for 36 months. Oral care in this patient population, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Many studies focus on the inadequate oral care that causes microbial accumulation; the standard oral care includes brushing the teeth with a toothpaste once a day and mouth washing with rinse solution [ 3 , 12 ]. Solutions for oral care vary among studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focus on the inadequate oral care that causes microbial accumulation; the standard oral care includes brushing the teeth with a toothpaste once a day and mouth washing with rinse solution [ 3 , 12 ]. Solutions for oral care vary among studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, transoral endotracheal or orogastric tubes not only cause the mouth to remain open and go dry but also make oral care difficult. [ 3 ] Moreover, mouth dryness is accelerated by restricted fluid intake brought about by respiratory, cardiac, or renal problems[ 4 ] as well as decreased salivation brought about by factors such as fever, diarrhea, burns, and narcotic therapy. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…A. vera has wound healing effect due to the presence of Glucomannan, a mannose-rich polysaccharide and gibberellin, a growth hormone, interacts with growth factor receptor on the fibroblast, thereby stimulating its activity and proliferation, which in turn increases collagen synthesis after topical and oral application. [ 4 22 ] In addition, the presence of glucomannan and acemannan activate macrophages, stimulate immune system, so A. vera has antibacterial and antiviral effects. [ 23 ] Moreover, it has anti-inflammatory effect and inhibits the cyclooxygenase pathway and reduces prostaglandin E2.…”
Section: Introductionmentioning
confidence: 99%
“…A study has showed that a significant number of patients hospitalized in the ICU had poor oral hygiene status at the time of admission. Instructions published by the Center for Disease Prevention and Control on the prevention of pneumonia in hospital highlighted the preparation and implementation of a comprehensive oral care program, which included the use of an antibacterial agent in areas where patients are prone to hospitalacquired pneumonia (Browne et al 2011;Scannapieco, Wang & Shiau 2001). Health and oral care should be considered as one of the most important parts of nursing care.…”
Section: Introductionmentioning
confidence: 99%